Corrosion behaviour of super-hydrophobic copper surfaces in 3.5% NaCI solution - Φούρκας, Βλάσιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Εργαστήριο Ναυπηγικής Τεχνολογίας, 2014)
A novel method for the formation of a composite super-hydrophobic film, composed of flower-like surface nanostructures, and how that innovative super-hydrophobic film affects corrosion behavior of the material, was studied within the present paper. The film was formed on fresh copper surface. The super-hydrophobic film was pretreated by myristic acid (n-tetradecanoic acid), (CH3(CH2)12COOH), chemically adsorbed onto the copper wafer. The film structure was probed with contact angle measurement (CA), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Moreover, the corrosion resistance of bare and modified samples in 3.5% NaCl, were investigated by Open Circuit and Potentiodynamic Polarization Measurements (PPM). Experimental results show that the corrosion resistance of Cu with super-hydrophobic surface was improved remarkably, because of its unique nanostructure. All experimental results proved that the super-hydrophobic surface can improve the corrosion resistance of copper significantly. The air trapped in the nano-crevices of the film was suggested to be responsible for the superior waterrepellent property.